Miliary tuberculosis leading to acute respiratory distress syndrome: Clinical experience in pediatric intensive care. Issue 12 (9th September 2019) - Piastra, Marco; Picconi, Enzo; Morena, Tony C.; Valentini, Piero; Buonsenso, Danilo; Conti, Giorgio; Antonelli, Massimo; Wolfler, Andrea M.; Chidini, Giovanna; Pons‐Òdena, Martí; De Pascale, Gennaro; ,
Abstract: Acute respiratory distress syndrome (ARDS) represents a rare complication of miliary tuberculosis (TB) in the adult setting, and it is even less common in the pediatric population. The presence of comorbidities and the possibility of a delayed diagnosis may further impair the clinical prognosis of critically ill patients with disseminated TB and acute respiratory failure. In this report, we present a case series of five pediatric patients with miliary TB and ARDS, where rescue and multimodal respiratory support strategies have been applied with a favorable outcome in more than half of them. The burden of miliary TB over time on a general pediatric intensive care unit—including two ARDS patients—is also illustrated.